Parameters Estimation of Lindely Distribution a Comparative Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study the three-parameter Lindley distribution (LD) and its mathematical and statistical propertiessuch as the moment generating function, quantile function, reliability function and others. And we estimate the parameters ofthis distribution by simulation study in eight methods; the maximum Likelihood (ML), ordinary least squares (OLS), methodof weighted least squares (WLS), percentiles method (P.C), method of maximizing distance multiplication (MDM), Anderson'sDarling (AD), Anderson from the right (RAD) and Cramer-von Mess (C-VM) method. According to the simulation study forthree types of samples, the maximum likelihood method was the best method, followed closed the Anderson Darling method,then the method of maximizing the multiplication of distances, we use the statistical criteria (BIAS, MSE, MRE), forcomparison between the methods.